2017
DOI: 10.1177/0263617417722253
|View full text |Cite
|
Sign up to set email alerts
|

Study of catalytic cracking process of fuel oil to obtain components of motor fuels using aerosol nanocatalysis technology

Abstract: The article presents the results of the investigation of catalytic cracking process of crude oil in a distillation column, under atmospheric pressure, the active component of the catalyst being type Y zeolite. The process was carried out under the conditions of a new technology, called ''aerosol nanocatalysis.'' A schematic diagram of the laboratory installation is described and comparison of the experimental data with thermal cracking processes is made, and the expected technical and economic indicators of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It should be noted that the phenomenon of the resonant effect of the intensity of mechanical activation, which includes cavitation, was observed for other technologies that employ mechanical methods for the selective energy supply to reaction centers. For example, a method known as "aerosol nanocatalysis" [15] implies the activation and formation of a constant concentration of the aerosol of hyperactive catalytic particles due to a change in the frequency of fluctuations of the catalytic system, consisting of a catalyst powder with initial dimensions up to 200 µm and a material that disperses this catalyst, whose dimensions are up to 1.2 mm. The study into various processes of hydrocarbon treatment involving this method revealed the presence of abnormal maximum dependences of the effective constant of cracking reaction rates at certain frequencies of fluctuations in the catalytic system, as well as a change in the yield of individual products.…”
Section: Analysis Of Experimental Data and Comparison Of Results Withmentioning
confidence: 99%
“…It should be noted that the phenomenon of the resonant effect of the intensity of mechanical activation, which includes cavitation, was observed for other technologies that employ mechanical methods for the selective energy supply to reaction centers. For example, a method known as "aerosol nanocatalysis" [15] implies the activation and formation of a constant concentration of the aerosol of hyperactive catalytic particles due to a change in the frequency of fluctuations of the catalytic system, consisting of a catalyst powder with initial dimensions up to 200 µm and a material that disperses this catalyst, whose dimensions are up to 1.2 mm. The study into various processes of hydrocarbon treatment involving this method revealed the presence of abnormal maximum dependences of the effective constant of cracking reaction rates at certain frequencies of fluctuations in the catalytic system, as well as a change in the yield of individual products.…”
Section: Analysis Of Experimental Data and Comparison Of Results Withmentioning
confidence: 99%
“…We studied the process of fuel oil refining at the laboratory installation for aerosol nanocatalysis described in works [18,19]. The laboratory installation consists of three basic nodes: a reagent feed node, a reaction node, a reaction product selection node.…”
Section: Materials and Methods To Study The Process Of Fuel Oil Refiningmentioning
confidence: 99%
“…As a result of the search, the choice focused on the new evolving technology of aerosol nanocatalysis. The technology has already proven successful in the processes of catalytic cracking of vacuum gasoil on zeolite catalysts [18]. In this regard, it should be noted that the complex physical and chemical characteristics of raw materials do not make it possible to use conventional catalytic systems in the process of fuel oil refining to a fraction of light hydrocarbons.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In this case, long-chain hydrocarbons in oil residue are broken down to simpler molecules as light hydrocarbons, by the breaking of carbon-carbon bonds at results of cracking process. As a result of the cracking process, this residue obtained a fuel fraction [14][15][16]. In addition, it has been shown that it is possible to increase the fuel fraction yield as a result of the cracking process of high paraffin oil residues in Mongolia.…”
Section: Figure 2 N-alkane Distribution Of Tsagaan-els Crude Oil and Atmospheric Residuementioning
confidence: 99%